Person Reference in Iranian Sistani Narrative Texts - Farideh Okati (مطالعات زبانی و بلاغی)
This paper is based on pragmatics and studies the person reference and referring devices in the Iranian Sistani folklore regarding the Accessibility approach. The study shows what the condition of applying reference is in the stories, and whether the employments of the different kinds of referring devices such as proper noun, pronoun, and zero anaphora is violating the general rules. Sistani is genetically related to the pro-drop language of Persian. The material was gathered from Sistan region in Iran by interviewing the consultants to narrate folktales and stories. The result shows that, apart from the frequent usage of proper noun for emphasis, the anaphoric zero has the highest range of occurrence and is the highest accessible marker in the context, and this violation, relating the ‘government and binding’ theory of Chomsky (1981), occurs because the discontinuity conditions, such as end of the clause-chain, does not force the anaphoric pronoun or proper noun to be used where they are expected to be. This is also shown by the statistical analysis, using Chi2 (P < 0.05). In the retrieval process, it is appeared that where zero anaphors are used, no matter how long is the distance between the anaphoric elements, there are no specific classifiers available to identify the referents more easily, and they are more or less accessible via the person markers in the verbs. And this is against Givon’s views (1983) of direct relation between little distance and the occurrence of a zero anaphors, and the principle of the usage of an NP. Concentration on the story by the listeners is crucial to cope with many zero anaphors to retrieve the referents, and this can show the long interest and concern of people in Sistani society with folktales and storytelling that has helped them to transfer this culture from generation to generation.